The KCa2 Channel Inhibitor AP14145, But Not Dofetilide or Ondansetron, Provides Functional Atrial Selectivity in Guinea Pig Hearts - Kirchhoff, Jeppe Egedal; Skarsfeldt, Mark Alexander; Muthukumarasamy, Kalai Mangai; Simó-Vicens, Rafel; Bomholtz, Sofia Hammami; Abildgaard, Lea; Jespersen, Thomas; Sørensen, Ulrik S.; Grunnet, Morten; Bentzen, Bo Hjorth; Diness, Jonas Goldin (Frontiers in Pharmacology, 2019)
Background and Purpose: Prolongation of cardiac action potentials is considered antiarrhythmic in the atria but can be proarrhytmic in ventricles if the current carried by Kv11.1-channels (IKr) is inhibited. The current mediated by KCa2-channels, IKCa, is considered a promising new target for treatment of atrial fibrillation (AF). Selective inhibitors of IK (dofetilide) and IKCa (AP14145) were used to compare the effects on ventricular and atrial repolarisation. Ondansetron which has been reported to be a potent blocker of both IKr and IKCa was included to examine its potential atrial antiarrhythmic properties. Experimental Approach: The expression of KCa2- and Kv11.1-channels in the guinea pig heart was investigated using qPCR. Whole-cell patch clamp technique was used to investigate the effects of dofetilide, AP14145, and ondansetron on IKCa and/or IKr. The effect of dofetilide, AP14145, and ondansetron on atrial and ventricular repolarisation was investigated in isolated hearts. A novel atrial paced in vivo guinea pig model was further validated using AP14145 and dofetilide. Key Results: AP14145 increased AERP without prolonging QTcB both ex vivo and in vivo. In contrast, dofetilide increased QTcB and, to a lesser extent, AERP in isolated hearts and prolonged QTcB with no effects on AERP in the in vivo guinea pig model. Ondansetron did not inhibit IKCa, but did inhibit IKr in vitro. Ondansetron prolonged ventricular, but not atrial repolarisation ex vivo. Conclusion and Implications: IKCa inhibition by AP14145 selectively increases atrial repolarisation whereas IKr inhibition by dofetilide and ondansetron increases ventricular repolarisation to a larger extent than atrial repolarisation.